Endovascular Occlusion of Traumatic Carotid Cavernous Fistula by Using Detachable Balloon in Various Ways: A Case Series - Srivastava, Trilochan; Husain, Shakir; Gandhi, Ashok; Sinha, Virendra D. (Indian Journal of Neurotrauma, 2017)
Introduction The detachable balloons are not frequently used nowadays for endovascular occlusion of carotid-cavernous fistula (CCF) because of lack of availability and supposed high risk of recurrence. This study describes the various way of detachable balloon embolization for traumatic CCF.Materials and Methods We have used endovascular detachable balloon to occlude the traumatic CCF under local anesthesia in various ways in 12 traumatic cases of CCF from March 2013 to April 2015. Clinical and computed tomographic (CT) angiography follow-up was done at 6 and 12 months.Results Clinical follow-up from 6 to 12 month showed persistent resolution of symptoms in 10 cases; 2 cases had developed slight proptosis and chemosis. CT angiography done in nine cases after 6 to 9 months showed no residual filling in CCF.Conclusion The detachable balloon either single or double with or without coils can be used in the management of CCF by different methods. Detachable balloon is a cheaper alternative compared with coiling. It is technically easier to perform and can be performed under local anesthesia.
Keywords: traumatic carotid-cavernous fistula; detachable balloons; endovascular management